Karboksimetil Kitosan Menurunkan Degranulasi Mast Cell yang Diinduksi Oleh Ovalbumin - Ibrahim, Mohamad Nur; Widjajanto, Edi; Permatasari, Nur; Sabarudin, Akhmad (Fakultas Kedokteran Universitas Brawijaya, 2009)
ABSTRACTOvalbumin is known as mast cell degranulating agent through the FCÎµRI aggregation. Carboxymethylchitosan (CMCs), a biocompatible cationic polymer was evaluated to reduces mast cell degranulation inducedby ovalbumin. In this experiment, wistar rats were darboxymethyl chitosanivided into 5 groups which consist of 1 control group and 4allergen groups. Among the allergen groups, 3 groups were treated with carboxymethyl chitosan/CMCs(doses : 0,25 mg, 0,50 mg and 1,00 mg) for 22 days. The result showed a significant (P<0,01) reduction inmast cell degranulation in allergen groups. This finding indicate that CMCs possesses antiinflammationactivity mediated by reducing of mast cell degranulation.Keywords : ,c mast cell degranulation